Adaptation and Validation of the Brief Sexuality Scale in Colombian and Spanish Populations (2016)
The Sexuality Scale is an instrument which evaluates what people think and how they feel about their own sexuality through three components: Sexual Self-Esteem, Sexual Depression and Sexual Preoccupation. Given the clinical implications and impact on sexual health after having demonstrated its relationship with various components of sexuality, and the little research on the last two components of the scale, this study undertook to translate, adapt and validate the brief version of the Sexuality Scale in a sample of 1167 Spanish and Colombian men and women. Two versions of the instrument were obtained-one for each country. In both versions, the results indicate high levels of reliability and adequate psychometric properties of the items. Configural invariance confirmed the three-dimensional structure of the scale for the two versions. The correlations with scales that evaluate various aspects of sexuality confirm adequate levels of concurrent validity. The scales may have important implications for evaluation and intervention of various dimensions of sexual behavior. © 2016 AAC.